Lifespan Development / Fifth Edition - Bee Helen; Boyd Denise (Pearson, 2009)
Pearson International Edition. Foundations, Basic Concepts and Methods, Theories of Development, Prenatal Development and Birth, Infancy, Cognitive Development in Infancy, Social and Personality Development in Infancy, Early Childhood, Physical and Cognitive Development in Early Childhood, Social and Personality Development in Early Childhood, Middle Childhood, Physical and Cognitive Development in Middle Childhood, Social and Personality Development in Middle Childhood, Adolescence, Physical and Cognitive Development in Adolescence, Social and Personality Development in Adolescence, Early Childhood, Physical and Cognitive Development in Early Childhood, Social and Personality Development in Early Childhood, Middle Childhood, Physical and Cognitive Development in Middle Childhood, Social and Personality Development in Middle Childhood, Late Adulthood and the End of Life, Physical and Cognitive Development in Late Adulthood, Social and Personality Development in Late Adulthood.